Earlier palliative home care is associated with patient-centred medical resource utilisation and lower costs in the last 30 days before death in COPD: a population-level decedent cohort study. Issue 5 (21st May 2020) - Scheerens, Charlotte; Faes, Kristof; Pype, Peter; Beernaert, Kim; Joos, Guy; Derom, Eric; Cohen, Joachim; Deliens, Luc; Chambaere, Kenneth
COPD patients often use many medical resources, such as hospital admissions and medical imaging, inappropriately close to death. Palliative home care (PHC) could beneficially affect this. The aim was to study the effect of use and timing of PHC on medical resource use and costs in the last 30 days before death (DBD) for COPD. We performed a retrospective study of all Belgian decedents in 2010–2015 with COPD and a primary cause of death being COPD or cardiovascular diseases. Odds ratios for medical resources were calculated between using and four PHC timing categories (>360, 360–181, 180–91 and 90–31 DBD) versus not using. Confounders were socio-demographic, care intensity and disease severity variables. Of the 58 527 decedents with COPD, 644 (1.1%) patients received PHC earlier than 30 DBD. Using PHC ( versus not using) decreased the odds ratio for hospitalisation (0.35), intensive care unit admission (0.16), specialist contacts (0.58), invasive ventilation (0.13), medical imaging including chest radiograph (0.34), sedatives (0.48) and hospital death (0.14). It increased the odds ratio for home care (3.27), general practitioner contact (4.65), palliative care unit admission (2.61), noninvasive ventilation (2.65), gastric tube (2.15), oxygen (2.22) and opioids (4.04) (p<0.001). Mean total healthcare costs were €1569 lower for using PHC. All PHC timing categories showed a benefit in medical resource use and costs. However, we observed the largest benefit in the category PHC 90–31 DBD. Health policy and services should focus on increasing PHC access, while research should further explore early PHC initiation for COPD. Palliative home care is associated with more patient-centred care and reduced costs in the final month of life for people with COPD http://bit.ly/2Pr2U1i